DEVELOPMENT OF IDEAS ABOUT COLLOIDAL DISPERSE SYSTEMS AND THEIR BASIC PROPERTIES - Yusufova Sabina Georgievna (Western European Studies, 2023)
The global role of colloids lies in the fact that they are the main components of such biological formations as living organisms. All substances in the human body are colloidal systems. Colloids enter the body in the form of nutrients and, during the digestion process, are converted into specific colloids characteristic of a given organism. This article learns about colloid-chemical human physiology which is a branch of science that studies the functioning of the human body systems that form colloidal compounds
Keywords: colloidal formations; phosphorus; membranes